Republic of Palau : Assessment of the Supervision and Regulation of the Financial Sector-Volume I; Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents key findings of the Assessment of the Supervision and Regulation of the Financial Sector for Palau. Palau's government has demonstrated a clear political commitment to antimoney laundering. In addition to being a signatory to the Honiara Declaration, it has more recently volunteered to participate in an initiative led by the Forum Secretariat and the Asia/Pacific Group on Money Laundering to assist the countries in the Pacific region to put in place effective measures for antimoney laundering, combating terrorism financing, and financial sector fraud.